PENGARUH LOCUS OF CONTROL TERHADAP KINERJA APARATUR PEMERINTAH KOTA LHOKSEUMAWE - MASLIANA MASLIANA; JAMALUDDIN JAMALUDDIN (LPPM STIE Lhokseumawe, 2015)
Target of this research to test influence of control of locus to performance of aparatur in government of town of Lhokseumawe. Population in this research is counted 32 SKPD exist in government of town of Lhokseumawe, and this research sampel is all public servant of civil in government of town of Lhokseumawe with amount of propagated kuesioner 100 responder. Analysis the used is analysis of regresi simple. As for intake of sampel in this research is to use method of profosional sampling. In data processing used by software of computer that is Statistical Product and Service Solution (SPSS) Version 16.0. Variable in this research is free variable of control of locus ( X), and performance of aparatur governmental (Y) represent variable tied, before examination of hypothesis done/conducted by examination of instrument covering validity test and test reliabilitas. Result of research indicate that control of locus have an effect on positive to performance of aparatur at government of town of Lhokseumawe.